MAKNA FASHION GENERASI Z DALAM FILM SUNSHINE BECOMES YOU ANALISIS SEMIOTIKA ROLAND BARTHEZ - Nur Rochmat Indiarjo; Sapto Hudoyo (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2021)
The research was meant to see through deeper about the signs that resides within the main actors’s costumes of Sunshine Becomes You as the fashion of Generation Z. The reseach method is descriptive and use Roland Barthes’s semiotic analysis about the denotative and connotative value of the signs. The conclusion of this research shows according to the signs from the main actors’s costume from Sunshine Becomes You that Generation Zs has a mindset of how very important look is for them, tend to be practice and instant behaviours, love freedom and high self-confidence, and also eagerly need for self-approvement from their society.